Hearts and Minds: War Neurosis and the Politics of Madness in Anna Kavan's I Am Lazarus. Issue 4 (2nd October 2017) - Walker, Victoria
Abstract: Anna Kavan's fictional portrayals of psychiatric breakdown and its treatment provide a unique perspective on the patient's experience of early to mid twentieth-century psychiatry. This article looks in detail at Kavan's time working with soldiers suffering from effort syndrome during the Second World War, observing how the solider-psychiatric patient becomes a figurehead for her radical politics in her Horizon article 'The Case of Bill Williams' (1944), and a prominent protagonist in her stories. Through close reading of her correspondence, her journalism and her wartime stories collected in I Am Lazarus (1945), it examines how the intersection of psychological trauma and physiological symptoms characteristic of effort syndrome surfaces in Kavan's writing of this period and in her own psychic responses to the war. It observes the importance of figurative language to her portrayal of war trauma and psychological breakdown, as her characters embody metaphor in their psychosomatic symptoms, and explores a twisted reconception of mind–body dualism prevalent throughout her writing of this period. It goes on to examine how the peculiar interaction of the physical and the psychological extends to the relationship between Kavan's characters and their external environment in her Blitz stories. Against the backdrop of the war-torn city, mind and body engage in ongoing conflict, affect and emotion bleed into her physical landscapes, and everyday objects become animated and hostile towards her protagonists.